The impact of transit-oriented development on heritage cities: A study of Haliç Metro and its influence on Istanbul’s urban fabric - Krismawanti; Destiawan, Wawan (Institute for Advanced Science Social, and Sustainable Future, 2025)
Background: Transit-Oriented Development (TOD) has emerged as a transformative approach to urban planning, aiming to balance modern infrastructure with sustainable urban growth. Methods: This study examines the impact of the Haliç Metro Köprüsü, a key component of Istanbul’s transit network, on the urban fabric of the Golden Horn—a heritage-rich area characterized by its historical and cultural significance. While the bridge has faced criticism for its modernist design and perceived disconnect from its surroundings, this research uncovers its latent potential to support placemaking strategies in heritage-sensitive contexts. Findings: The findings reveal that the Haliç Metro Köprüsü successfully enhances connectivity across Istanbul’s European districts, reducing congestion and providing efficient mobility for thousands of daily commuters. Its strategic location serves as a transit hub that links historically significant neighborhoods such as Balat and Galata, fostering economic activity and improving accessibility to cultural landmarks. Conclusion: The research highlights the need for targeted placemaking interventions, such as enhancing pedestrian pathways, integrating public art reflective of local history, and activating adjacent spaces for cultural events. These strategies could elevate the bridge’s role from a functional transit corridor to a vibrant public space that harmonizes modern infrastructure with Istanbul’s heritage identity. Novelty/Originality of this article: The study contributes new insights into the potential of TOD projects to act as catalysts for placemaking in heritage cities. By leveraging TOD principles and culturally sensitive urban design, infrastructure like the Haliç Metro Köprüsü can bridge the gap between modern urban needs and the preservation of historical identity, ensuring inclusive and sustainable development.